METAL 2020 Conference Proeedings 2020
DOI: 10.37904/metal.2020.3496
|View full text |Cite
|
Sign up to set email alerts
|

INCEFA-PLUS Project: Review of the test programme and main results

Abstract: INCEFA-PLUS (INcreasing Safety in NPPs byCovering gaps in Environmental Fatigue Assessment) project characterized environmentally assisted fatigue of stainless steels in light water reactor environments. During this project more than 200 fatigue tests have been carried out in different laboratories across Europe in air and water environment. Most tests were performed on a single batch of 304L, an austenitic stainless steel alloys employed in NPPs. The tests addressed the effects of strain amplitude, hold time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…For tests in air, holds were added at 6000 cycle intervals starting from the 6000th cycle for strain range 0.3% and 1000 cycle intervals starting from the 1000th cycle for 0.6%. Preliminary analysis including Phase II tests ( [40,42], confirmed in Section 3.1.3) suggested that there was no observable effect of hold times for the tested conditions, although beneficial effects of hold time on fatigue life have been reported by the AdFaM (Advanced Fatigue Methodologies) project [13].…”
Section: Sub-programme On Hold Timesmentioning
confidence: 95%
“…For tests in air, holds were added at 6000 cycle intervals starting from the 6000th cycle for strain range 0.3% and 1000 cycle intervals starting from the 1000th cycle for 0.6%. Preliminary analysis including Phase II tests ( [40,42], confirmed in Section 3.1.3) suggested that there was no observable effect of hold times for the tested conditions, although beneficial effects of hold time on fatigue life have been reported by the AdFaM (Advanced Fatigue Methodologies) project [13].…”
Section: Sub-programme On Hold Timesmentioning
confidence: 95%